Experiences of EFL Lecturers Using Collaborative Teaching in Speaking Classes at the Higher Education Level - Raja Mahendra Tanjung; Mukhlash Abrar; Noprival (Jurnal Multidisipliner Bharasumba, 2026)
This study investigates the factors contributing to EFL students’ reluctance to speak English during classroom discussions and explores the strategies they use to overcome this issue. A qualitative case study was conducted with eight students from the English Education Study Program at a public university in Jambi Province, selected through purposive sampling. Data were collected through semi-structured interviews and analyzed using Braun and Clarke’s (2006) thematic analysis. The findings reveal three major factors underlying students’ reluctance: linguistic factors (limited vocabulary, pronunciation difficulties, and grammatical constraints), psychological factors (fear of making mistakes, criticism, nervousness, low self-confidence, and low self-esteem), and learning-related factors (unsupportive learning environments, difficult course materials, and limited speaking practice). To address these challenges, students employed strategies such as rehearsing before speaking, writing ideas beforehand, seeking peer assistance, and actively listening during discussions, which helped reduce anxiety and improve confidence.